(3fXe LhGgQ GdCQHYjf aj CUhd GdOjfs - (3GdQVj GdZRj, eMeO Hf eMeO Hf CMeO, J (B935 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj JYQa dYHGOg GdPjf TQaG dYQahg HGdcJGH GdefRd Ydi GdfHj GdgGTej GdeaVds
(3BNQgG (B:s
(3hef jcf eJUaG eY PGJg HOj GdUaGJ cGjf UaGJg MjGO dcf HMjGI YGdeG HGdYde bGOQG HbOQceGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 56s
(3eYLe GdeDdajf (B3 / 622s
(3TPQGJ GdPgH (B8 / 209s
(3gOjI GdYGQajf (B2 / 233s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs